Assessing Ploidy Level Analysis and Single Pollen Genotyping of Diploid and Euploid Citrus Genotypes by Fluorescence-Activated Cell Sorting and Whole-Genome Amplification - Garavello, Miguel; Cuenca, José; Dreissig, Steven; Fuchs, Jörg; Houben, Andreas; Aleza, Pablo (Frontiers in Plant Science, 2019)
Fluorescence-Activated Cell Sorting (FACS), whole genome amplification (WGA) and genotyping were combined to analyse the genetic composition of single pollen nuclei of different citrus species. Genotyping with SSR and SNP molecular markers resulted in a call rate comparable with those previously reported for several other species. We have identified in the ‘CSO’ tangor an additional nuclei population composed by the vegetative plus generative nuclei and the presence of unreduced gametes in the diploid genotype ‘Mexican’ lime. We further discuss the importance and applications of single pollen genotyping in Citrus genetic studies.